Carcass characteristics and meat quality of finishing gilts fed diets with different levels of SID methionine + cystine and Vitamin B6 supplementation - Sangali, Cleiton Pagliari; Gasparino, Eliane; De Paula, Vinícius Ricardo Cambito [UNESP]; Ferreira, Silvia Letícia; Campos, Bruno; Leite, Natália Galoro; Furlan, Antonio Cláudio; Pozza, Paulo Cesar (Universidade Estadual de Londrina, 2018)
This study was carried out to evaluate the effects of different levels of standardized ileal digestible (SID) methionine + cystine (Met + Cys) and vitamin B6 supplementation on the carcass characteristics and longissimus lumborum (LL) quality in gilts from 75 to 100 kg. Fifty-six gilts were used (Talent x Topigs 20), with an initial average body weight of 75.06 ± 1.68 kg, allotted in a completely randomized block design arranged in a 2×4 factorial scheme, composed of two vitamin B6 supplementation levels (1.58 and 3.58 mg/kg) and four levels of SID Met + Cys (0.370, 0.470, 0.570, and 0.670%), with seven replicates and one animal per experimental unit. No interactions (P > 0.05) between vitamin B6 supplementation and SID Met + Cys levels were observed. The levels of SID Met + Cys and vitamin B6 supplementation did not affect the carcass characteristics. Thawing loss increased linearly, and a quadratic effect was observed for cooking loss and shear force of the LL when dietary SID Met + Cys levels increased. The highest cooking loss (27.29%) and shear force (21.58 N) were estimated at 0.528 and 0.539% SID Met + Cys levels, respectively. The dietary SID Met + Cys requirement for gilts (75–100 kg) did not exceed 10.60 g/day (0.37%), based on carcass characteristics and meat quality parameters, and was not affected by vitamin B6 supplementation.
Keywords: Backfat thickness; Cooking loss; Lean yield; Meat colour; Sulphur amino acids